Identification of Moci Ibu Ade's MSME Business Opportunities Challenges based on an Islamic Perspective in Ciderum Village - Fitriyani, Metty; Husna Asri, Kholifatul; Arby, Abbas (Neolectura, 2024)
This research was conducted on the basis of a survey conducted in Ciderum Village Rt 04 Rw 03. Identifying business opportunity challenges plays a very important role in a business. Identifying business challenges is done to identify potential risks and prevent them before they become serious problems, and identifying business opportunities helps businesses to take actions that can generate growth and profits for businesses, especially MSMEs. MSMEs are a form of business that has been implemented by some people in Ciderum village. According to the survey, there are several types of MSMEs such as toddler fish, woven bamboo baskets, and moci in Ciderum Village, specifically in Batu twin Village. The aim of this research is to identify the challenges of business opportunities that exist in Mrs. Ade's Moci MSME location. The method used is a qualitative method by interviewing Mrs. Ade herself as the moci maker. The results of this interview show that Mrs. Ade has been marketing her moci for 20 years, but due to her age, Mrs. Ade does not understand the developments and opportunities that exist today. By conducting interviews, Mrs. Ade began to understand the importance of identifying business opportunity challenges such as challenges to increase knowledge and skills, business plans, behavior of MSME entrepreneurs, increasing creativity and innovation, knowing obstacles to business opportunities, and individual success. By identifying the challenges of the MSME Moci business opportunity, Mrs. Ade began to think about implementing it with the aim of developing Moci products such as providing training to employees, utilizing online sales techniques, and collaborating with other business networks to expand sales reach.